THE URGENCY OF TEXTUAL CRITICISM OF THE NEW TESTAMENT INERRANCY - Valentino Wariki; Gernaida Krisna R. Pakpahan (Phronesis: Jurnal Teologi dan Misi, 2022)
Textual criticism has long existed as part of the hermeneutic discipline. However, many communities reject this approach. Even scientifically, textual criticism provides a new understanding of the scriptures, especially the New Testament. The many variants of the Greek New Testament make textual criticism present to reconstruct the original text of the Greek New Testament. Nevertheless, on the other hand, this scientific development deals with the doctrine of the inerrancy of the Bible. This study attempts to present the logical foundations of the urgency of textual criticism related to the doctrine of the inerrancy of the Bible. This study examines the importance of textual criticism of the inerrancy of the Bible. The approach used is exploratory qualitative. The results showed that the hermeneutic method of textual criticism did not weaken the truth of the Bible. The inerrancy of the Bible is maintained when an interpreter uses this method. The meaning of the text is more understandable and far from error because of the approach to the highlighted New Testament Greek.